The Direction of Police Community Policy In The Prevention of Traffic Accidents In Polda Metro Jaya - Antariksawan, Rudi; Mustofa, Muhammad (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractThere are three core functions of the police, law enforcement, order maintenance, and services to the community or public services. One part of the law enforcement function is preventing and overcoming traffic violations. Traffic accidents have a large and detrimental impact, and this is one of many indicators of the success of the police. Traffic accidents are often caused by drivers who do not obey the rules, so they endanger themselves or others. In addition to violations by drivers, other things that become the factor occurrence of traffic accidents are road quality, human error, and vehicle worthiness. The purpose of this study was to determine the direction of community policing policies in dealing with traffic violations, and efforts to develop community policing models by paying attention to public participation and the role of the police in preventing traffic violations. The results obtained show that significant factors that caused the occurrence of high accidents per population were factors related to drivers or human factors, where the dominant violation was a violation of the speed limit. By knowing that the main factor of accidents is the human element, the policies taken to overcome this are policies related to humans, namely community policing.Keywords: Police Community, Traffic Violations, Traffic Accidents AbstrakAda tiga fungsi inti polisi; penegakan hukum, pemeliharaan pesanan, dan layanan kepada komunitas atau layanan publik. Salah satu bagian dari fungsi penegakan hukum adalah mencegah dan mengatasi pelanggaran lalu lintas. Kecelakaan lalu lintas memiliki dampak yang besar dan merugikan, dan ini adalah salah satu dari banyak indikator keberhasilan polisi. Kecelakaan lalu lintas sering disebabkan oleh pengemudi yang tidak mematuhi aturan, sehingga membahayakan diri mereka sendiri atau orang lain. Selain pelanggaran oleh pengemudi, hal lain yang menjadi faktor terjadinya kecelakaan lalu lintas adalah kualitas jalan, kesalahan manusia, dan kelayakan kendaraan. Tujuan dari penelitian ini adalah untuk menentukan arah kebijakan pemolisian masyarakat dalam menangani pelanggaran lalu lintas, dan upaya untuk mengembangkan model pemolisian masyarakat dengan memperhatikan partisipasi publik dan peran polisi dalam mencegah pelanggaran lalu lintas. Hasil yang diperoleh menunjukkan bahwa faktor signifikan yang menyebabkan terjadinya kecelakaan tinggi per populasi adalah faktor yang berhubungan dengan faktor pendorong atau manusia, dimana pelanggaran dominan adalah pelanggaran batas kecepatan. Dengan mengetahui bahwa faktor utama kecelakaan adalah unsur manusia, kebijakan yang diambil untuk mengatasinya adalah kebijakan yang terkait dengan manusia, yaitu pemolisian masyarakat.Kata kunci: Komunitas Polisi, Pelanggaran Lalu Lintas, Kecelakaan Lalu Lintas АннотацияСуществуют три основные функции полиции: правоохранительные органы, сохранение порядка и обслуживание населения или общественных служб. Одна из функций правоохранительных органов - это предотвращение и преодоление нарушений правил дорожного движения. Дорожные происшествия оказывают большое и пагубное влияние и являются одним из многих показателей успеха работы полиции. Дорожные происшествия часто вызваны водителями, которые не подчиняются правилам, поэтому они подвергают опасности себя или других. Помимо нарушений со стороны водителей, другим факторами, которые становятся причинами дорожных происшествий, являются качество дороги, человеческая ошибка и качество автомобиля. Цель этого исследования состояла в том, чтобы определить направление политики Совместной Охраны Порядка (Community Policing) в борьбе с нарушениями правил дорожного движения и усилия по разработке моделей Совместной Охраны Порядка, уделяя внимание участию общественности и роли полиции в предотвращении нарушений правил дорожного движения. Полученные результаты показывают, что значительными факторами, которые стали причиной большого количества аварий на одного человека, были факторы, связанные с водителями или человеческими факторами, где доминирующим нарушением было нарушение ограничения скорости. Так как основным фактором является человеческий, меры, предпринимаемые для его преодоления, являются мерами, связанными с людьми, а именно с Совместной Охраной Порядка.Ключевые слова: Полицейское сообщество, Нарушение правил дорожного движения, Дорожные происшествия